P245 Monitoring the uptake and early impact of targeted hpv vaccination among men who have sex with men (msm) attending gum and hiv clinics in england. (8th June 2017) - Checchi, Marta; Mesher, David; McCall, Mark; Chau, Cuong; Panwar, Kavita; Beddows, Simon; Soldan, Kate
Abstract : Introduction: MSM are at high risk for HPV infection and associated disease (genital warts and anal, oropharyngeal, and penile cancers). Additionally, MSM will receive little or no herd protection from the existing national vaccination programme for females. Following Joint Committee on Vaccination and Immunisation (JCVI) advice, a targeted HPV MSM vaccination pilot was introduced in GUM and HIV clinics across England from June 2016. We present plans for monitoring vaccination uptake and surveillance of infection and early disease outcomes. Methods: Uptake (of three doses over a two year period) will be monitored via two existing surveillance and reporting systems: the Genitourinary medicine clinic activity dataset (GUMCADv2) and the HIV and AIDS reporting system (HARS). A seroprevalence study conducted in selected clinics for validation of these data will be considered in due course. Early impact of targeted HPV vaccination of MSM on the epidemiology of HPV infection will be detected by HPV DNA testing of rectal swabs (residual specimens following chlamydia testing) from MSM attending selected GUM clinics, starting with largely baseline collection in 2017. Expected early effects on genital warts diagnoses will be monitored (via GUMCADv2). A decline in HPV-associated cancers is not expected to be seen for some years. Discussion: A comprehensive surveillance strategy has been established to evaluate targeted HPV vaccination of MSM at GUM/HIV clinics. During the pilot, uptake will be the main outcome measure available, and surveillance systems will be established and baseline data collected to evaluate the outcomes of national implementation on infection and disease.